The Development of Prosocial Behavior in Counseling College Students - Muhammad Fadlan; Herman Nirwana (International Journal of Applied Counseling and Social Sciences, 2025)
Prosocial behavior is selfless helping behavior that reflects moral maturity, so it is important for students to possess, especially prospective guidance counselors or counselors. Guidance counseling students are required to have a high level of prosocial attitude because their future profession focuses on mentoring, assisting, and developing individual potential. This study aims to describe the development of prosocial behavior among guidance counseling students at Padang State University. The method used was descriptive comparative with a sample of 450 students from the first to fourth years. Data analysis was performed through descriptive statistics, ANOVA, and Post Hoc tests using computer services. The results showed that the prosocial behavior of Guidance and Counseling students at Padang State University was in the high category. However, the development from year to year did not show a progressive pattern. Therefore, the Guidance and Counseling Department needs to devise strategic steps so that students' prosocial behavior can develop sustainably from the early semesters of their studies. The benefits of this study are to contribute to the development of social psychology by examining the development of prosocial behavior among Guidance and Counseling students, as well as to serve as a reference for further research in understanding the factors that influence prosocial behavior.